Design of UHF RFID Tag Antenna for Metallic Surfaces - Miao, Shijie; Wang, Peng; Liu, Zhenhua; Hao, Qiaohong; Qu, Weiyi (Scientific Journal of Technology, 2026)
To address the challenges of information exchange and enable real-time status monitoring of components awaiting remanufacturing, this paper presents a semi-flexible UHF RFID tag antenna designed for direct mounting on metallic objects. Numerical simulations were conducted to analyze the transmission coefficient and mutual impedance patterns, achieving conjugate impedance matching between the antenna and the chip, thereby establishing the desired resonant frequency. The antenna's resonant frequency can be conveniently adjusted via coarse and fine tuning of specific geometric parameters. Experimental validation, conducted according to a predefined protocol, measured the antenna's resonant frequency in both free-space and on-metal environments. The results demonstrate maximum read ranges of 11.5 m on a metal-free surface and 6.2 m on an aluminum alloy steel pipe, with the resonant frequency consistently maintained within the 860 MHz to 960 MHz range. The proposed antenna exhibits robust anti-metal characteristics, making it highly suitable for application on large metallic surfaces commonly found in remanufactured products.